2004
DOI: 10.1128/aem.70.6.3558-3565.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Rate of Attachment of Listeria monocytogenes , Pantoea agglomerans , and Pseudomonas fluorescens to, and the Probability of Their Detachment from, Potato Tissue at 10°C

Abstract: The rate of attachment of bacteria to, and their subsequent detachment from, the cut surface of raw potato tissue was measured and modeled by using mathematical approaches that allowed detailed objective comparisons of adhesion processes under different conditions. Attachment was rapid and reached equilibrium after contact for 60 min. A new method to measure the probability of detachment was developed and modeled, revealing that the probability of detachment for Pseudomonas fluorescens remained unchanged for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…To detect any possible antilisterial activity during the attachment period, actual initial concentrations on sliced carrots were compared with theoretical values. Such theoretical concentrations have been estimated here from an expression developed for Listeria cells attached to potato disks, which do not show antilisterial activity and were prepared following the same procedure as described here (Garrood et al, 2004). The number of L. monocytogenes cells becoming attached to both sides of the potato disks has been reported in the mentioned work as proportional to the inoculum concentration (expressed as CFU mL -1 ) raised to the power of 0.79 (CFU per potato disk= 1.418 × [inoculum size] 0.79 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect any possible antilisterial activity during the attachment period, actual initial concentrations on sliced carrots were compared with theoretical values. Such theoretical concentrations have been estimated here from an expression developed for Listeria cells attached to potato disks, which do not show antilisterial activity and were prepared following the same procedure as described here (Garrood et al, 2004). The number of L. monocytogenes cells becoming attached to both sides of the potato disks has been reported in the mentioned work as proportional to the inoculum concentration (expressed as CFU mL -1 ) raised to the power of 0.79 (CFU per potato disk= 1.418 × [inoculum size] 0.79 ).…”
Section: Resultsmentioning
confidence: 99%
“…After 40 min, enough time for attachment (Garrood, Wilson & Brocklehurst, 2004), batches of ten carrot disks were rinsed in 1 L of sterile PSDF (at 10 or 25°C, respectively) for 1 min, stirring at 150 rpm. The purpose of this step was to simulate the domestic washing and at the same time to remove bacteria that were loosely associated with, but had not adhered to, the carrot tissue.…”
Section: Preparation Of Carrot Disks and Measurement Of Antilisterialmentioning
confidence: 99%
“…By contrast, studies on Salmonella and Listeria attachment to animal (chicken, beef, pork) food surfaces (Benedict, Schultz, & Jones, 1991;Chung, Dickson, & Crouse, 1989;Notermans & Kampelmacher, 1974;Dickson & Macneil, 1991) have been conducted since the 1970s. More recently studies on the attachment of these bacteria to fruits (Pao & Davis, 2001), vegetables (Barak, Whitehand, & Charkowski, 2002;Ells & Hansen, 2006;Garrood, Wilson, & Brocklehurst, 2004;Gorski, Palumbo, & Mandrell, 2003;Iturriaga, Escartin, Beuchat, & Martinez-Peniche, 2003) and fish (Kim & Marshall, 2001;Kim & Marshall, 2002;Verhaegh, Marshall, & Oh, 1996) have been reported. Although information on the attachment of Salmonella and Listeria to shrimp is very limited, we speculate that the process is similar to that associated with meat and plant products.…”
Section: Attachment and Persistence Of Salmonella And Listeria On Shrimpmentioning
confidence: 98%
“…Garrood et al (54) found that an increase in time of contact enhanced the attachment of L. monocytogenes, Pantoea agglomerans, and P. fluorescens to potato tissue. Longer contact times also reduced the probability of detachment of bacterial cells from potato surfaces, indicating that the strength of bacterial attachment to surfaces may increase over time (54). For Campylobacter, we recently reported that increasing temperature and time of contact both increases the numbers of C. jejuni cells attaching to stainless steel and decreases the probability of detachment of bacterial cells from this surface (118).…”
Section: Environmental Factors Some Environmental Factors Such As Tementioning
confidence: 99%